Explaining differences in the returns to R&D in Argentina: The role of contextual factors and complementarities - Arza, Valeria (2020)
Argentina’s private investment in research and development is well below that of its peers. One important reason may be low and very heterogeneous returns to research and development activities on productivity. This paper uses novel microdata to estimate the returns to research and development and understand the contextual factors that shape their heterogeneity. The paper groups these context-based factors into knowledge complementary factors (that is, factors that affect the returns via learning capabilities from external sources of knowledge) and market complementary factors (factors that act via business capabilities to appropriate the returns to research and development investments). The paper hypothesizes that the effects of contextual factors depend on firms’ management capabilities and attitudes (innovative capacity), which determine firms’ ability to benefit from the context. The findings suggest that the returns are indeed heterogeneous across regions and sectors, and these results depend on some context-based factors, which can boost or depress the returns to R&D. The results have important policy implications, considering the effectiveness of innovation policies, need for adapting to specific regions and sectors, and maximization of the impact of these factors on the returns to research and development.